Cultural Tourist Market Reference for Destination Management Saung Angklung Mang Udjo Bandung, Jawa Barat - Nugraha, Rizki Nurul; Dewi, Liliana (Westscience Press, 2025)
Indonesia has a lot of attractive tourism destinations, which are natural destinations, cultural destinations, and also man-made destinations. West Java, especially Bandung City which is usually called Paris Van Java, has so many attractive tourism destinations, one of the famous tourism destinations is cultural destinations. Every Tourist has a dream to visit Bandung, to enjoy the exoticism of Bandung. One of the famous cultural destinations is called